SYNTHESIS OF BLACK TITANIA USING MICROWAVE-ASSISTED HYDROGEN PLASMA - Wildan Azzindani, Muhammad
The demand for efficient and environmentally friendly catalysts continues to increase along with the development of industry and technology. One of the promising materials to be developed as a photocatalyst is titania. However, the main weakness of titania material is the large bandgap energy, which results in low absorption efficiency in the visible light region. One solution that can be done is to transform titania into black titania, which has a narrower bandgap energy and more efficient absorption in the visible light region. Therefore, in this research, black titania was synthesized using hydrogen plasma under vacuum pressure. The precursor used was Aeroxide Degussa P25 titania, which was soaked with water to form a slurry. Black titania was synthesized by reducing titania using hydrogen plasma with a hydrogen gas flow rate of 40 sccm and a pressure in the plasma reactor chamber of 2-3 Torr. The synthesized black titania with variations in synthesis duration are darkening in color. Raman characterization of the black titania shows the rutile phase with a small portion of the anatase phase. Meanwhile, the UV-Vis diffuse reflectance spectroscopy (DRS) characterization shows an increase in the visible light absorption for synthesis durations above 1 minute. This is also supported by the results of photoluminescence spectroscopy characterization, which shows peaks due to the presence of radiative electron recombination processes, originating from new electronic levels due to crystal defects caused by oxygen vacancies. The synthesized black titania was then applied as a catalyst in the rhodamine B photodegradation process. The black titania showed an efficiency of 21-40% within 30 minutes. Overall, the effect of hydrogen plasma treatment has an impact on the phase changes and the formation of crystal defects in titania.